Lake, of the East London Fed. of Suffragettes, speaking at Trafalgar Square on occasion of the strike at C. & E. Morton's pickle, jam, sweet tin-making and tea-packing factory (1914)
Lake, of the East London Fed. of Suffragettes, speaking at Trafalgar Square on occasion of the strike at C. & E. Morton's pickle, jam, sweet tin-making and tea-packing factory.